Ownership structure and firm performance: The role of R&D - Ting I.W.K.; Kweh Q.L.; Lean H.H.; Ng J.H. (Faculty of Economics and Administration, 2023)
This study aims to examine the impact of ownership structure (i.e. family ownership, government ownership, and foreign ownership) on firm performance, viz. Tobins Q and return on assets. The impact of R&D on the relationship between ownership structure and firm performance is also assessed using a sample of 201 Malaysian public listed companies for the period of 2002-2011. Findings show that family ownership and foreign ownership positively relate to firm performance, but not government ownership. More importantly, R&D strengthens the relationship between family ownership and foreign ownership with firm performance respectively. While prior studies have shown that ownership structure is related to firm performance, this paper contributes to a new understanding of the role of R&D in moderating the relationship between ownership structure and firm performance. 2016, Faculty of Economics and Administration. All rights reserved.